Peran Mikrobiota Usus Terhadap kondisi Obesitas - Armanto Makmun; Wialda Dwi Rodya; Zulfahmidah Zulfahmidah; Windy Nurul Aisyah Aisyah (Indonesian Journal of Health, 2020)
The gut microbiota has been recognized as an important factor in the development of metabolic diseases such as obesity and is considered an endocrine organ involved in the maintenance of energy homeostasis and immunity. Intestinal dysbiosis can alter gastrointestinal peptide production associated with satiety, resulting in increased food intake. In obese people, this dysbiosis appears to be associated with increased gut microbiota has been implicated in the control of food intake and satiety via intestinal peptide signaling, in which bacterial products activate enteroen-docrine cells by modulating enterocyte-produced paracrine signaling molecules. The gut microbiota can increase the production of certain SCFAs, which have been shown to be associated with increased production of YY (PYY) peptides, ghrelin, insulin, and glucagon-like peptide-1 (GLP-1). The purpose of this study was to Article Review by looking at the topic of the gut microbiota and obesity by using research with quantitative meta-analysis methods based on previous research. This research method uses the article review method. The data source of this research comes from literature obtained via the internet in the form of research results from international journals in 2010-2020. The results of this study from a total of 50 journals, which the authors have reviewed, concluded that the role of the gut microbiota in energy regulation, studies have linked the gut microbiota with the pathogenesis of insulin resistance and inflammation in obesity. It is known that obesity is associated with low-grade chronic inflammation and insulin resistance. The gut microbiota has been implicated in the control of food intake and satiety through intestinal peptide signaling, in which bacterial products activate enteroen-docrine cells by modulating the enterocyte-produced paracrine signaling molecules. The conclusion of this study based on the results of the study found that the effect of intestinal microbiotas on obesity.